Sikap Moderat Mufassir Terhadap Riwayat Isra’iliyyāt - Abdur Rokhim (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Mufassir's Moderate Attitude to The History of Isra'iliyyātThis research aims to examine isra'iliyyāt and the commentators who use it, amidst the incessant attacks and rejection of the use of isra'iliyyāt in interpreting the Qur'an. Understanding isra'iliyyāt is very important because it can control radicalism and extremism. This study uses a qualitative method based on data sourced from classical and contemporary commentary books, by examining the opinions of scholars who accept and reject isra'iliyyāt. As well as several new studies published in the journal. This study found that some commentators are moderate in the use of isra'iliyyāt, by selecting and being critical. It is true that there is resistance to the use of isra'iliyyāt, but the mufassir who accept and use isra'iliyyāt are far more numerous than the mufassir who refuse. Among the isra'iliyyat users are those who are moderate, namely selective and critical of the use of isra'iliyyat.